Karakteristik Mikroplastik pada Water Treatment Plant (WTP) Perumda Tirta Merangin - Desi Karlina; Siti Umi Kalsum; Marhadi Marhadi (Universitas Batanghari Jambi, 2026)
Microplastics have been identified in rivers that supply raw water, particularly the Batang Merangin River, which supplies 90% of the treated water for Perumda Tirta Merangin. This situation has raised concerns about microplastic contamination in treated water. This study aims to describe the attributes of microplastics at the Water Treatment Plant (WTP) of Perumda Tirta Merangin, Merangin Regency. The study used a quantitative descriptive and experimental approach, examining water samples from each treatment unit (raw water intake, coagulation, flocculation, sedimentation, filtration, and reservoir) at the Ecoton Laboratory in Gresik. The results identified three categories of microplastics: fibers (47 particles), filaments (38 particles), and fragments (5 particles), for a total of 90 particles. The dominant color of microplastics was blue (39%), with sizes ranging from 2 mm.